2014
DOI: 10.1080/14767724.2014.944757
|View full text |Cite
|
Sign up to set email alerts
|

Deskilling and delanguaging African migrants in Barcelona: pathways of labour market incorporation and the value of ‘global’ English

Abstract: This article analyses the labour and social trajectories of seven multilingual and well-educated young men from Africa in the Barcelona area (Catalonia, Spain) over a 5-year period. Our data consist of life history interviews combined with ethnographic observations in a settlement non-governmental organisation (NGO). We adopt a critical sociolinguistic perspective on language and mobility which underlines the time-space dimension of migrants' emplacement and understands the value of global languages in relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…At a micro/individual level, such studies enrich knowledge in their attempts to better understand the conditionalities, mechanisms and impacts of immigrants' over-education, as well as the (non-)utilisation of their human capital, and more broadly, the international migration movements of highly-skilled persons (e.g. Rye and Andrzejewska, 2010;Aure, 2013;Raghuram and Kofman, 2004;Webb, 2015;Sert, 2016;Garrido and Codóc, 2017).…”
Section: Data and Methodological Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…At a micro/individual level, such studies enrich knowledge in their attempts to better understand the conditionalities, mechanisms and impacts of immigrants' over-education, as well as the (non-)utilisation of their human capital, and more broadly, the international migration movements of highly-skilled persons (e.g. Rye and Andrzejewska, 2010;Aure, 2013;Raghuram and Kofman, 2004;Webb, 2015;Sert, 2016;Garrido and Codóc, 2017).…”
Section: Data and Methodological Approachmentioning
confidence: 99%
“…For the purposes of this article, the term can -in a simplified way -be defined as a state in which an individual possesses a higher level of education than is required by their job position, or requirements connected with acquiring a new job (Koutná, 2016;Green and Zhu, 2010). On the basis of a literature review, it seems that overqualification, discrimination, and inequality have become inseparable parts of immigrants' working activities in the labour markets of many destination countries (see the examples in: Chiswick and Miller, 2009;Aleksynska and Tritah, 2013;Spoonley, 2006;Nowotny, 2016;McDonald and Valenzuela, 2016;Garrido and Codóc, 2017;Gupta and Man, 2014;Lagana, 2011;Man, 2004;Spielvogel and Meghnagi, 2018). Though many factors may be behind this situation, Ho and Alcorso (2004) and others (e.g.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These academic studies, quantitative in nature, point at deficient language skills and related social skills as one of the barriers to employment (Ho, 2007; Stevens, 2005; Syed and Murray, 2019) overlooking the existence of a particular national migration regime in relation with the labor market (Nawyn, 2016) and its impact on the value assigned to language. Yet, some researchers have also found that the host country language level of migrants does not have a particular positive effect (Duchêne, 2016; Flubacher et al, 2017; Garrido and Codó, 2017), nuancing celebratory discourses about language as a key to employment and upward social mobility.…”
Section: Surplus Population Linguistic Market and Profit Within The Capitalist Mode Of Productionmentioning
confidence: 99%
“…The academic field is dominated by the human capital approach, which links skills and qualifications to employment opportunities and tries to explain the success of certain individuals and not others, based on language ability. Yet, some researchers have also found that host country language level does not play a role in the emplacement of migrants, with the exception of the dwindling NGO and tourism sectors (Garrido and Codó, 2017). Additionally, despite possessing highly valued language skills, even English, qualified migrants with tertiary educational qualifications often still undergo declassing and downward professional mobility (Sert, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As Canadian research (Creese & Wiebe, 2012) on tertiary educated sub-Saharan migrants with excellent English language skills has shown, employment agencies tend to guide migrants to entry-level jobs instead of helping them to build a long-term career strategy. Garrido and Codó (2017) found that African migrants in Barcelona had appropriated the dominant 'tabula-rasa' discourses and thus disregarded their education and language skills and aimed at low-skilled jobs, although their reason for coming to Spain had been to study further. The migration services in general and employment offices in particular should carefully consider how educated migrants could be supported in finding appropriate employment, because that would facilitate both purposeful language learning and integration into Finland.…”
Section: Resultsmentioning
confidence: 99%